1994
DOI: 10.1111/j.1365-2958.1994.tb00989.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of transcription termination by RNA poiymerase I

Abstract: SummaryEukaryotic ribosomal gene transcription units are bordered at their 3 ends by short DNA sequences which specify site-specific termination by RNA polymerase i (poii). Poll terminators from yeast through to mammals appear to follow similar rules: they contain a site for a sequence-specific DNA-binding protein; they function only in one orientation; 3 ends are formed upstream of the binding site; and 5 fianking sequences influence the position and efficiency of 3 end formation. Recent progress in understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Furthermore, this orientation specificity is also not without precedent. Reb1, the yeast terminator for RNAP1, shares the Myb-like DNA binding domain and functions as a terminator in only the forward orientation with regard to transcription (Reeder and Lang 1994). Consistent with this model, we observed a large decrease in RNAP II occupancy downstream of the Rap1p site found within our CO-Ty1 element that did not occur when the Rap1p site was replaced with native Ty1 sequence.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, this orientation specificity is also not without precedent. Reb1, the yeast terminator for RNAP1, shares the Myb-like DNA binding domain and functions as a terminator in only the forward orientation with regard to transcription (Reeder and Lang 1994). Consistent with this model, we observed a large decrease in RNAP II occupancy downstream of the Rap1p site found within our CO-Ty1 element that did not occur when the Rap1p site was replaced with native Ty1 sequence.…”
Section: Discussionsupporting
confidence: 75%
“…Better known as the terminator for RNA polymerase I, the main role of Reb1p is to pause that polymerase at the release element, a role that can mostly be replaced by a heterologous DNA binding roadblock such as the lac repressor (Jeong et al 1995). Interestingly, like Rap1p, the DNA binding domain of Reb1p is similar to that of the Myb oncoprotein and likewise is only capable of pausing transcription in an orientation-specific manner (Reeder and Lang 1994). In humans, the transcription factor MAZ shares similarities with Rap1p, and is found to bind to promoters as well as to pause RNAP II transcription (Ashfield et al 1994;Yonaha and Proudfoot 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The boxed sequence is predicted to span a membrane (16 (17,26). This observation is in keeping with the absence of homology between these terminators (26). As expected from the similarities of transcription between the procyclin, VSG, and ribosomal units (7), we found that the PARP A termination region was able to inhibit CAT activity driven by the VSG and ribosomal promoters, although this effect was reproducibly weaker in case of the VSG promoter.…”
Section: Discussionsupporting
confidence: 63%
“…S.L., splice leader acceptor site. The boxed sequence is predicted to span a membrane (16 (17,26). This observation is in keeping with the absence of homology between these terminators (26).…”
Section: Discussionsupporting
confidence: 54%
“…How does the Reb1 TTD terminate transcription? Our data suggest an active mechanism promoted by physical interactions between Reb1 TTD and RNA pol I rather than a passive roadblock imposed by the tight binding of Reb1 to Ter DNA sites (7,47,48). To determine which subunit(s) of RNA pol I interacted with Reb1, we took advantage of the S. pombe genetic database (www.…”
Section: Resultsmentioning
confidence: 99%